Quantitative Effect of Zr Content on the Structure and Water–Gas Shift Reaction Activities of Gold Supported on Ceria–Zirconia - Li Song (Crystals, 2018)
Effect of Zr content on the structure and water–gas shift reaction catalytic activities of Au-CeO2-ZrO2 catalysts were quantitatively analyzed in detail. For the low ZrO2 content (0–15 wt. %), the Ce-Zr-O solid solutions were formed through the substitutional incorporation of Zr cations into CeO2 lattice, resulting in the contraction of cell parameters a and d-spacing (i.e., lattice distortion) and the increase of microstrain and oxygen vacancies. Quantitatively, the enhanced WGS activities have good linear correlation with the cell parameters a, microstrain, Raman shift and oxygen vacancies. Whereas, for the rich-zirconia (45 wt. %) sample, Au-CeZr-45 has some isolated t-ZrO2 and fluorite CeO2 instead of solid solution. The isolated t-ZrO2 crystallites block the contact between Au and CeO2, resulting in the agglomeration of gold clusters and, as a consequence, poor WGS activity of Au-CeZr-45 catalyst.